2018
DOI: 10.1186/s41983-018-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin-like growth factor 1 (IGF-1) in multiple sclerosis: relation to cognitive impairment and fatigue

Abstract: BackgroundMultiple sclerosis (MS) is a chronic demyelinating central nervous system (CNS) disease. Changes in insulin growth factor 1 (IGF-1) input to the brain can affect survival of myelin and CNS cells. The study aims to investigate the relation of serum IGF-1 levels with cognitive impairment and fatigue in MS patients.MethodsThis study was conducted on 46 MS patients and 46 healthy controls. All participants were subjected to clinical assessment, serum IGF-1 levels, expanded disability status scale (EDSS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Our results on the concentrations of IGFs and IGFBPs in serum generally correspond to previous findings in MS patients (20,21). Compared to other studies in MS patients (22)(23)(24), but also to published reference concentrations (25), we found higher IGF-I concentrations in the serum of our patients. The reason for this could be related to differences in severity and stage of the disease, therapeutic interventions, different age, and gender distributions, and, last but not least, to different analytical techniques.…”
Section: Compounds From the Insulin-like Growth Factor System In Serusupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on the concentrations of IGFs and IGFBPs in serum generally correspond to previous findings in MS patients (20,21). Compared to other studies in MS patients (22)(23)(24), but also to published reference concentrations (25), we found higher IGF-I concentrations in the serum of our patients. The reason for this could be related to differences in severity and stage of the disease, therapeutic interventions, different age, and gender distributions, and, last but not least, to different analytical techniques.…”
Section: Compounds From the Insulin-like Growth Factor System In Serusupporting
confidence: 91%
“…A previous study showed that after aerobic training, the serum concentrations of IGF-I in MS patients are significantly correlated with muscle strength (left and righthand strength, quadriceps strength) and walking speed (19). Low levels of IGF-I in the circulation were further associated with fatigue and cognitive impairment in MS patients (24). The positive effects of repeated TCA injections on serum concentrations of IGF-I and on the ratio of IGF-I to IGFBPs in serum from MS patients may thus have relevance for physical and cognitive functions.…”
Section: Effects Of Triamcinolone Acetonide Applicationmentioning
confidence: 98%
“…IGF-1 not only plays an important role in the development of T2DM (Rajpathak et al, 2009), but also is a pluripotent growth factor with multiple functions in the peripheral and central nervous system. It supports neuronal survival and axon growth, and also acts on myelinating Schwann cells and oligodendroglia, which is an important stimulus for myelin membrane formation (Liang et al, 2007; Nageeb et al, 2018). Rauskolb found the expression of IGF-1 and its corresponding receptor IGF-1R are dysregulated in patients with diabetes and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I likely play a fundamental role in the myelination process. Low serum IGF-1 levels correlated with cognitive impairment and fatigue in MS patients [ 39 ]. In our study, we did not observe any differences in baseline IGF-1 levels or changes following whole body cryotherapy ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%